Hybrid Laser-Arc Welding Tanks Steels. Issue 1 (April 2016) - Turichin, G; Tsibulskiy, I; Kuznetsov, M; Akhmetov, A; Klimova-Korsmik, O
Abstract: The results investigate hybrid laser-arc welding of high strength steels using design responsible metallic construction and the highest strength body of vehicles. Welds from modern high strength steels grade Hardox 400, Hardox 450, Armox 600T and AB were created. High power fiber laser LS-15 with output 15 kW and arc rectifier VDU - 1500 DC were used in the experiment. Results of the metallographic research and mechanical tests are presented.